2018
DOI: 10.1038/s41598-018-34030-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and toxicity of bevacizumab, endostar and apatinib in transgenic and human lung cancer xenograftzebrafish model

Abstract: The poor prognosis in non-small-cell lung cancer has driven the development of novel targeted therapies. Vascular endothelial growth factor is the most potent force in mediating tumor angiogenesis, and many angiogenesis inhibitors have been developed for oncology treatment. We performed a study to characterize the efficacy, safety and tumor suppression of three lung cancer related anti-angiogenic drugs (bevacizumab, endostar and apatinib) using transgenic zebrafish embryo and human lung cancer xenotransplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Besides, the tested four DKPs had a promising antitumor effect on HT-29 xenograft zebrafish. In agreement with our findings, three anti-angiogenic drugs such as bevacizumab, endostar, and lapatinib were demonstrating a remarkable inhibition of tumor growth in a xenografted zebrafish model within a nonlethal dose range 44 . Fu and co-workers reported that pan-phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002 significantly reduced the xenograft tumor size in zebrafish by decreasing the viability of metastatic cancer cells 45 .…”
Section: Discussionsupporting
confidence: 92%
“…Besides, the tested four DKPs had a promising antitumor effect on HT-29 xenograft zebrafish. In agreement with our findings, three anti-angiogenic drugs such as bevacizumab, endostar, and lapatinib were demonstrating a remarkable inhibition of tumor growth in a xenografted zebrafish model within a nonlethal dose range 44 . Fu and co-workers reported that pan-phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002 significantly reduced the xenograft tumor size in zebrafish by decreasing the viability of metastatic cancer cells 45 .…”
Section: Discussionsupporting
confidence: 92%
“…In animal models, the antitumor activity of Endostar is more preponderant than bevacizumab, while they show comparative antiangiogenic effects . The traditional method of Endostar administration reduces patient compliance and affects quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A zebrafish subintestinal vessel angiogenesis assay was performed according to a previously reported method . Zebrafish embryos were injected with different concentrations of Tp47 (22, 44 or 88 ng/fish) or PBS (control group).…”
Section: Methodsmentioning
confidence: 99%